2010
DOI: 10.1002/bbb.206
|View full text |Cite
|
Sign up to set email alerts
|

Poplar as a feedstock for biofuels: A review of compositional characteristics

Abstract: The growing demand for transportation fuels, along with concerns about the harmful effects of greenhouse gas emissions from the burning of fossil fuels, has assured a viable future for the development of alternative fuels from renewable resources, such as lignocellulosic biomass. The effi cient utilization of these biomass resources is critically dependant on the in-depth knowledge of their chemical constituents. This, together with the desired fuel properties, helps tailor the chemical and/or enzymatic proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
439
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 593 publications
(465 citation statements)
references
References 67 publications
20
439
0
6
Order By: Relevance
“…High expression levels of glycosyl hydrolases in lignocellulosic biomass are required to achieve full auto-hydrolysis in standard conditions. Using poplar as an example, under the assumption that soluble proteins in poplar are about 90 mg/g dry weight [125] and cellulose in wood is 450 mg/g dry weight [44], it is anticipated that levels of more than 14 % TSP cellulase will be required to be produced in and recovered from poplar leaf to completely hydrolyze host plant cellulose ( Table 2).…”
Section: The Need For Enhanced Specialized Expression Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression levels of glycosyl hydrolases in lignocellulosic biomass are required to achieve full auto-hydrolysis in standard conditions. Using poplar as an example, under the assumption that soluble proteins in poplar are about 90 mg/g dry weight [125] and cellulose in wood is 450 mg/g dry weight [44], it is anticipated that levels of more than 14 % TSP cellulase will be required to be produced in and recovered from poplar leaf to completely hydrolyze host plant cellulose ( Table 2).…”
Section: The Need For Enhanced Specialized Expression Systemsmentioning
confidence: 99%
“…Tree species, such as poplar and willow, could be planted as biomass crops on marginal land. These trees share characteristics, such as fast growth rate, easy propagation, and high biomass production in a short time, that make them suitable as bioenergy crops [44,45]. Perennial grasses such as switchgrass, reed canary grass, Napier grass, and Bermuda grass have low fertilizer requirements and established management systems, making them suitable for the production of biomass for biofuels [46].…”
Section: Introductionmentioning
confidence: 99%
“…It is a challenge to obtain high operational flexibility at power plants by application of a broad biofuel range. Therefore, poplar, which is among the fastest growing trees in the world, was selected for this study [15]. The moisture content and bulk density were measured using standard methods described in EN ISO 18134-1:2015 and EN ISO 17828:2015.…”
Section: Introductionmentioning
confidence: 99%
“…Poplar is well known for its large wood production, ability to adapt to different environments, and integration and synergy with agriculture Sannigrahi et al, 2010;SFA, 2013). Traditionally, poplar plantations have always been established for timber production Vietto et al, 2011;Xiao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, poplar plantations have always been established for timber production Vietto et al, 2011;Xiao et al, 2013). Logically, it would be ideal for carbon sequestration purposes (Cannell and Milne, 1995;Xiao et al, 2013) and as a bioenergy supplier for mitigating climate change (Kauter et al, 2003;Sannigrahi et al, 2010;Sevigne et al, 2011;Wright, 2006). Xiao et al (2013) analyzed the carbon sequestration capabilities of different ecosystems in China and reported that poplar plantations in subtropical China have a higher capability than other forest ecosystems in other regions of China.…”
Section: Introductionmentioning
confidence: 99%